Effect of the thickness of quasi one-dimensional zinc oxide nanorods synthesized via multiple growth process under ammonia assisted hydrolysis technique on the performance of dye-sensitized solar cell - Umar A.A.; Rahman M.Y.A.; Taslim R.; Salleh M.M.; Oyama M. (2023)
Vertical array quasi ZnO nanorods is synthesized on FTO coated glass substrate via a one-dimensional crystal growth of attached-nanoseeds in an aqueous solution containing zinc acetate and ammonia at room-temperature. The growth processes are carried out at five different cycle growth process (one to five times) in order to obtain quasi one-dimensional ZnO nanorods with various morphologies in terms of diameter and length of the nanorod. These quasi ZnO nanorods are coated with cis-bis (isothiocyanato)bis (2,20-bipyridyl-4, 40-dicarboxylato)-ruthenium (II) bis-tetrabutylammonium dye (N719) and are then used as photovoltaic material of dye-sensitized solar cell (DSSC). FESEM results show the diameter and length of ZnO nanorod increase with the number of growth cycle. The UV absorption spectra show that the optical absorption increases with the length of ZnO nanorods coated with the dye. The Jsc of the cell is increased by increasing the length of the nanorods up to the optimum length of 180 nm. The highest Jsc and Voc of 0.72 mAcm-2 and 0.6 V under illumination of 100 mWcm-2 light were obtained for the cell with the ZnO nanorods synthesized with 3rd growth cycle.